CONNECTION BOOK AND WORKSHEET BASED 2013 CURRICULUM FOR SD TEACHERS IN SURAKARTA - Marmoah, Sri; Soegiyanto, Soegiyanto; Atmojo, Idam Ragil Widianto; Ardiansyah, Roy (Universitas Sebelas Maret, 2018)
The purpose of this service is to train primary school teachers in Surakarta city to have the ability to optimize the role of a teacher to involve parents and the community in the implementation of learning so that specifically this activity aims to train teachers to have the ability to compile contact books and worksheets. The method used in this service begins the Workshop, Practices, and Implementation. In conducting this training, subjects were asked to work on tests related to the preparation of connection books and worksheets for elementary school teachers. Analysis of the data used is pre-test and post-test. The results of this activity were an increase in teacher's knowledge and understanding of the preparation of connection books and worksheets